Laboratory criteria of the obstetrical antiphospholipid syndrome - Boffa, Marie-Claire; Boinot, Catherine; De Carolis, Sara; Rovere-Querini, Patrizia; Aurousseau, Marie-Hélène; Allegri, Flavio; Nicaise-Roland, Pascale; Barra, Anne; Botta, Angela; Ambrozic, Ales; Avcin, Tadej; Tincani, Angela (Thrombosis and Haemostasis, 2009)
A debate on updating the laboratory criteria of antiphospholipid syndrome (APS) was recently opened in view to lower the risk of over diagnosis of the syndrome. Based on data related to thrombotic APS, it proposes the exclusion of anticardiolipin antibodies (aCL) and anti-beta2-glycoprotein 1 (a-β2-GPI) IgM detection. Here, we examine this possibility in a study which focuses on obstetrical APS (OAPS).We report new data on a prospective multicenter European cohort of 109 pregnant women having APS.Among them, 73 had purely obstetrical APS, not associated to autoimmune diseases or thrombosis. Isolated antibodies and isolated aCL positivity were present in 50/109 (46%) and in 34/109 (31%) of the women, respectively. An isolated a-β2-GPI IgM was present in three women.These results suggest that aCL and a-β2-GPI IgM cannot be dropped for the diagnosis and classification of OAPS.The low level of some antibodies associated with severe obstetrical complications raise the issue of keeping or not the same laboratory criteria for OAPS and for thrombotic APS and whether additional criteria after large prospective studies could further improve diagnosis.
Keywords: Anticardiolipin antibody; anti-beta2-glycoprotein I antibody; obstetrical antiphospholipid syndrome; thrombotic antiphospholipid syndrome; antiphospholipid syndrome diagnosis